Leadership Strategies and Practices in Facing Corruption Challenges in the Era of Digitalization 5.0 and Social Media - Elis Nurhayati; Hari Z Soeratin (Zona Education Indonesia, 2023)
Corruption is a worrying problem in many countries. Apart from causing harm to state finances, acts of corruption also undermine institutional integrity, impede social and economic progress, and impede people's welfare. The purpose of this study is to examine in depth the role of leadership in accelerating efforts to combat corruption in the digitalization 5.0 era and the social media era. In addition, this research also aims to find other leadership strategies and practices that are effective in dealing with corruption challenges in this context. The method applied in this study is a qualitative method. Some of the findings obtained from this study include: (1) leadership responsibility (2) leadership policies and practices (3) monitoring and evaluation (4) application of information technology and (5) involvement in social media.